If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-5+6(3+x)=3x+9
We simplify the equation to the form, which is simple to understand
x-5+6(3+x)=3x+9
Reorder the terms in parentheses
x-5+(+18+6x)=3x+9
Remove unnecessary parentheses
+x-5+18+6x=+3x+9
We move all terms containing x to the left and all other terms to the right.
+1x+6x-3x=+9+5-18
We simplify left and right side of the equation.
+4x=-4
We divide both sides of the equation by 4 to get x.
x=-1
| 2x+4y=65 | | -6*a+3=-3(2*a-1) | | 14=2(7+6y) | | 13x-102=-7x-207 | | 3(2p-8)-7(4p-2)=10p-6+9p | | 6x-4=2x-16 | | 4lnx-6lny= | | 3y-1=7y+17 | | 8x-5+4y=m | | 2(35-2y)+4y=70 | | -3*c-12=-5+c | | 10-6y=-32 | | S/-9=9 | | 3+2(5n-1)=21 | | 8y+6=9y-8 | | 8x-5=5y | | 5/9*1/12 | | C/4=20 | | X^2/3-3x-4=0 | | 2/5=-7 | | 7(3x+4)=2(5x+14) | | 7x+18=78 | | 7x=y-8 | | z/9-6=z/12 | | (z/9)-6=(z/12) | | X+9=6m | | 1.5x= | | 7m=x+6 | | h=-16t^2+145t+40 | | 1/7(-14x-2) | | h=-16t^2+145t-20 | | m=x+9 |